12(x-4)-8(2x-7)=3(x+5)

Simple and best practice solution for 12(x-4)-8(2x-7)=3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(x-4)-8(2x-7)=3(x+5) equation:


Simplifying
12(x + -4) + -8(2x + -7) = 3(x + 5)

Reorder the terms:
12(-4 + x) + -8(2x + -7) = 3(x + 5)
(-4 * 12 + x * 12) + -8(2x + -7) = 3(x + 5)
(-48 + 12x) + -8(2x + -7) = 3(x + 5)

Reorder the terms:
-48 + 12x + -8(-7 + 2x) = 3(x + 5)
-48 + 12x + (-7 * -8 + 2x * -8) = 3(x + 5)
-48 + 12x + (56 + -16x) = 3(x + 5)

Reorder the terms:
-48 + 56 + 12x + -16x = 3(x + 5)

Combine like terms: -48 + 56 = 8
8 + 12x + -16x = 3(x + 5)

Combine like terms: 12x + -16x = -4x
8 + -4x = 3(x + 5)

Reorder the terms:
8 + -4x = 3(5 + x)
8 + -4x = (5 * 3 + x * 3)
8 + -4x = (15 + 3x)

Solving
8 + -4x = 15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8 + -4x + -3x = 15 + 3x + -3x

Combine like terms: -4x + -3x = -7x
8 + -7x = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0
8 + -7x = 15 + 0
8 + -7x = 15

Add '-8' to each side of the equation.
8 + -8 + -7x = 15 + -8

Combine like terms: 8 + -8 = 0
0 + -7x = 15 + -8
-7x = 15 + -8

Combine like terms: 15 + -8 = 7
-7x = 7

Divide each side by '-7'.
x = -1

Simplifying
x = -1

See similar equations:

| 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 | | -5(-5z)=150 | | 4n+3=86 | | -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) | | (-4,3)M,=1/2 | | X/7=9=15 |

Equations solver categories